2014
DOI: 10.1007/s11904-013-0194-4
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks, Sexual Networks and HIV Risk in Men Who Have Sex with Men

Abstract: Worldwide, men who have sex with men (MSM) remain one of the most HIV-vulnerable community populations. A global public health priority is developing new methods of reaching MSM, understanding HIV transmission patterns, and intervening to reduce their risk. Increased attention is being given to the role that MSM networks play in HIV epidemiology. This review of MSM network research studies demonstrates that: (1) Members of the same social network often share similar norms, attitudes, and HIV risk behavior leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
135
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(144 citation statements)
references
References 89 publications
6
135
1
2
Order By: Relevance
“…Participants in the forum provided and received social support, and influenced one another, factors cited as critical in creating peer norms and behaviors including attitudes about sexual risk behaviors [41]. Future considerations include better understanding the way in which the expatriate and traveler network functions (both on and offline), including cohesion, density and homophily [85][86][87].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants in the forum provided and received social support, and influenced one another, factors cited as critical in creating peer norms and behaviors including attitudes about sexual risk behaviors [41]. Future considerations include better understanding the way in which the expatriate and traveler network functions (both on and offline), including cohesion, density and homophily [85][86][87].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research regarding HIV risk and the social and sexual networks of men who have sex with men has suggested that networks create an environment with shared behavioral norms and risk characteristics [41]. Communities such as this forum existing predominantly online, gradually develop norms as members get to know each other and start to debate and agree on what is acceptable [42].…”
Section: Comparison With Prior Workmentioning
confidence: 99%
See 1 more Smart Citation
“…8 y Amirkhanian y cols. 9 , en especial en la poblaciĂłn transexual 10 . Como conclusiĂłn, en nuestra serie la epidemia sigue teniendo predominio en grupos de riesgo, de sexo masculino y en zonas urbanas.…”
Section: Discussionunclassified
“…Individuals who demonstrate positive social support tend to have higher medication adherence, are more likely to disclose their HIV status to partners and loved ones, have lower transmission rates, stronger immune systems and better health, and are less likely to be socially isolated (Kingori, Haile, & Ngatia, 2015;Amirkhanian, 2014;Glick & Golden, 2014;De et al, 2013;Casale & Wild, 2013;Rao et al, 2012). Without social support, individuals who are HIV-positive are more likely to experience high rates of stress, anxiety, depression, guilt, shame, and substance use (Kingori, Haile, & Ngatia, 2015;Cortes, Hunt, & McHale, 2014).…”
Section: Social Supportmentioning
confidence: 99%